Power mobility for children: a survey study of American and Canadian therapists' perspectives and practices. (28th June 2018) - Kenyon, Lisa K; Jones, Maria; Livingstone, Roslyn; Breaux, Becky; Tsotsoros, Jessica; Williams, Kelly M
Abstract : Aim: To explore the views and practices of paediatric occupational therapists and physical therapists in Canada and the USA regarding the implementation of power mobility for children with mobility limitations. Method: This descriptive study utilized a web‐based survey that included questions pertaining to therapists' decisions to trial and use power mobility, agreement or disagreement with statements developed from published practice considerations regarding power mobility, and the frequency of performing tasks related to power mobility prescription and training. Results: Most respondents reported that child characteristics (e.g. cognition, safety awareness) were important factors in decision‐making about power mobility, whereas other child characteristics (e.g. communication abilities, age) were not as important. Family resources and home accessibility were also not considered important. The average age at which respondents considered power mobility for children was 2 years 3 months. The majority of respondents agreed with statements developed from published practice considerations and most frequently performed various power mobility tasks twice a year or less. Interpretation: Although most respondents appeared to have positive views regarding power mobility, few appeared to actively perform power mobility tasks in their practice. Resources to support therapists in the early introduction of power mobility may be beneficial. What this paper adds: Occupational and physical therapists positively view early introduction of power mobility for children with mobility limitations. Few therapists actively provide early power mobility experiences. Power mobility training and monitoring power mobility devices are important therapist roles. What this paper adds: Occupational and physical therapists positively view early introduction of power mobility for children with mobility limitations. Few therapists actively provide early power mobility experiences. Power mobility training and monitoring power mobility devices are important therapist roles. This article is commented on by Rodby‐Bousquet on pages969–970 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.